Al-Intiqaiyyah Method to Improve Maharah Al-Qira'ah Skills in Arabic Language Learning - Asse, Ahmad; Ahmad, Ahmad; Jabir, Muh; Idhan, Mohamad; Harun, Ubay (LETIGES, 2024)
This study aims to analyze the application of the al-intiqaiyyah method to improve Arabic reading skills (maharah al-qira’ah) in grade VIII Islamic Junior High School (MTs) students. This study fills the gap in previous studies by focusing on improving reading skills and exploring the flexibility of eclectic methods in adjusting learning to students' needs. This study uses a descriptive qualitative approach to analyze the application of the al-intiqaiyyah method in maharah al-qira’ah learning at State Islamic Junior High School (MTsN) 2 Palu City. Data were obtained through interviews, observations, and documentation, then analyzed using condensation techniques, data presentation, and concluding. Data validity was tested through triangulation of sources and methods. Implementing the al-intiqaiyyah method in maharah al-qira’ah learning at MTsN 2 Palu City involves three stages: preparation, implementation, and evaluation. This eclectic method combines audiolingual, grammar-translation, and task-based learning approaches to improve students' understanding of Arabic texts, pronunciation, and vocabulary. Evaluation is carried out through formative and summative assessments. As a result, students can understand sentence structures, apply grammar rules, and improve their speaking and writing skills through practical exercises. This approach supports a deeper and more applicable understanding of learning Arabic. This study was limited to minimal supporting facilities and a sample from one school, so the results are less generalizable. Further research is recommended to test the eclectic method in various schools with different conditions, expand the use of technology, and explore its impact on other language skills.